The differential effects of acute vs. chronic stress and their combination on hippocampal parvalbumin and inducible heat shock protein 70 expression - Filipović, Dragana; Zlatković, J.; Gass, Peter; Inta, Dragos (Neuroscience, 2013)
The hippocampus plays a central role in stress-related mood disorders. The effects of acute vs. chronic stress on the integrity of hippocampal circuitry in influencing the vulnerability to, or resiliency against, neuronal injury are poorly understood. Here we investigated whether acute vs. chronic psychosocial isolation stress or a combination of the two (chronic stress followed by acute stress) influences the expression of the interneuronal marker parvalbumin (PV) and the chaperone-inducible heat shock protein 70 (Hsp70i) in different subregions of the hippocampus. Low levels of the Ca2+-binding protein (PV) may increase the vulnerability to neuronal injury, and Hsp70i represents an indicator of intense excitation-induced neuronal stress. Adult male Wistar rats were exposed to 2h of immobilization (IM) or cold (4°C) (acute stressors), 21d of social isolation (chronic stress), or a combination of both acute and chronic stress. Both chronic isolation and the combined stressors strongly decreased the PV-immunoreactive cells in the CA1, CA3 and dentate gyrus (DG) region of the hippocampus, while acute stress did not affect PV expression. The combination of acute and chronic stress induced a dramatic increase in Hsp70i expression in the DG, but Hsp70i expression was unaffected in acute and chronic stress alone. We also monitored serum corticosterone (CORT) levels as a neuroendocrine marker of the stress response. Acute stress increased CORT levels, while chronic isolation stress compromised hypothalamic-pituitary-adrenocortical (HPA) axis activity such that the normal stress response was impaired following subsequent acute stress. These results indicate that in contrast to acute stress, chronic isolation compromises the HPA axis and generates a considerable reduction in PV expression, representing a decrease in the calcium-buffering capacity and a putatively higher vulnerability of specific hippocampal interneurons to excitotoxic injury. The induction of Hsp70i expression in response to acute and chronic isolation reveals that neurons in the DG are particularly vulnerable to an acute stressor following a chronic perturbation of HPA activity.